2016
DOI: 10.1002/hep.28406
|View full text |Cite
|
Sign up to set email alerts
|

Activation of liver X receptor/retinoid X receptor pathway ameliorates liver disease in Atp7B−/− (Wilson disease) mice

Abstract: Wilson disease (WD) is a hepatoneurologic disorder caused by mutations in the copper-transporter ATP7B. Copper accumulation in the liver is a hallmark of WD. Current therapy is based on copper chelation, which decreases the manifestations of liver disease, but often worsens neurologic symptoms. We demonstrate that in Atp7b−/− mice, an animal model of WD, liver function can be significantly improved without copper chelation. Analysis of transcriptional and metabolic changes in samples from WD patients and Atp7b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
79
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 42 publications
11
79
0
Order By: Relevance
“…; Hamilton et al . ). At this stage, genes involved cell cycle machinery and DNA repair are prominently up‐regulated (Ralle et al .…”
Section: Rodent Modelsmentioning
confidence: 97%
See 3 more Smart Citations
“…; Hamilton et al . ). At this stage, genes involved cell cycle machinery and DNA repair are prominently up‐regulated (Ralle et al .…”
Section: Rodent Modelsmentioning
confidence: 97%
“…; Hamilton et al . ). Macroscopic changes in the liver of Atp7b −/− mice can be seen at 7 months, with irregular shapes and regeneration nodes apparent (Buiakova et al .…”
Section: Rodent Modelsmentioning
confidence: 97%
See 2 more Smart Citations
“…At this age, the mice have evidence of elevated hepatic copper, but liver disease has not yet developed. (1) We were able to prevent the development of liver disease using the liver X receptor (LXR)/retinoid X receptor agonist, yet we did not affect hepatic copper (which remained high). We have not yet been able to definitively show how copper disrupts LXR-mediated lipid metabolism in animals, but in vitro experiments have shown that copper can alter nuclear receptor signaling.…”
mentioning
confidence: 95%